(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article deals with the main components of the tax on residential property, which are defined by the Tax Code of Ukraine, analyzed the current trends of taxation of housing, a list of objects subject to taxation and the main changes in granting and receiving privileges when making a tax, the main disadvantages of the functioning of the tax on residential real estate and directions of their elimination were proposed, factors influencing the efficiency of the tax system as a whole and on its separate components were determined, an assessment was made according to I th tax on residential real estate in Ukraine is one of the main sources of local budgets and regional development. Particular attention is paid to the current transformational processes in the tax system of the country when writing an article. It is researched that at present Ukraine is one of the few countries in the world in which the real estate taxation system is in the early stages of development. In the direction of reforming the tax system, most measures focus on decentralizing budget revenues, as they will be able to provide local authorities with sufficient financial resources to achieve their goals. In the context of the implementation of regional fiscal policy, it has been substantiated that tax revenues account for a significant share in filling local budgets of Ukraine. However, given the volatile economic situation in the country, problems associated with the insufficient financial base of local budgets and their significant dependence on transfers from the state budget are becoming even more urgent. At this stage of reforming the tax system one of the most important areas is the formation of a new and effective mechanism for taxation of residential property. It should provide for the realization and adjustment of the fiscal potential of the housing tax.